Contemporary use trends and survival outcomes in patients undergoing radical cystectomy or bladder‐preservation therapy for muscle‐invasive bladder cancer. Issue 22 (25th July 2017) - Cahn, David B.; Handorf, Elizabeth A.; Ghiraldi, Eric M.; Ristau, Benjamin T.; Geynisman, Daniel M.; Churilla, Thomas M.; Horwitz, Eric M.; Sobczak, Mark L.; Chen, David Y. T.; Viterbo, Rosalia; Greenberg, Richard E.; Kutikov, Alexander; et al.
Abstract : BACKGROUND: The current study was performed to examine temporal trends and compare overall survival (OS) in patients undergoing radical cystectomy (RC) or bladder‐preservation therapy (BPT) for muscle‐invasive urothelial carcinoma of the bladder. METHODS: The authors reviewed the National Cancer Data Base to identify patients with AJCC stage II to III urothelial carcinoma of the bladder from 2004 through 2013. Patients receiving BPT were stratified as having received any external‐beam radiotherapy (any XRT), definitive XRT (50‐80 grays), and definitive XRT with chemotherapy (CRT). Treatment trends and OS outcomes for the BPT and RC cohorts were evaluated using Cochran‐Armitage tests, unadjusted Kaplan‐Meier curves, adjusted Cox multivariate regression, and propensity score matching, using increasingly stringent selection criteria. RESULTS: A total of 32, 300 patients met the inclusion criteria and were treated with RC (22, 680 patients) or BPT (9620 patients). Of the patients treated with BPT, 26.4% (2540 patients) and 15.5% (1489 patients), respectively, were treated with definitive XRT and CRT. Improved OS was observed for RC in all groups. After adjustments with more rigorous statistical models controlling for confounders and with more restrictive BPT cohorts, the magnitude of the OS benefit became attenuated on multivariate (any XRT: hazard ratio [HR], 2.115 [95% confidence interval [95% CI], 2.045‐2.188]; definitive XRT: HR, 1.870 [95% CI, 1.773‐1.972]; and CRT: HR, 1.578 [95% CI, 1.474‐1.691]) and propensity score (any XRT: HR, 2.008 [95% CI, 1.871‐2.154]; definitive XRT: HR, 1.606 [95% CI, 1.453‐1.776]; and CRT: HR, 1.406 [95% CI, 1.235‐1.601]) analyses. CONCLUSIONS: In the National Cancer Data Base, receipt of BPT was associated with decreased OS compared with RC in patients with stage II to III urothelial carcinoma. Increasingly stringent definitions of BPT and more rigorous statistical methods adjusting for selection biases attenuated observed survival differences. Cancer 2017;123:4337‐45 . © 2017 American Cancer Society . Abstract : In the National Cancer Data Base, the receipt of bladder‐preservation therapy appears to be associated with decreased overall survival compared with treatment with radical cystectomy in all patients with stage II to III urothelial carcinoma of the bladder. The use of increasingly stringent definitions of bladder‐preservation therapy along with more rigorous statistical methods attenuates the observed overall survival differences.